3d printed continuous fiber reinforced composite auxetic honeycomb structures. (15th April 2020) - Quan, Chao; Han, Bin; Hou, Zhanghao; Zhang, Qi; Tian, Xiaoyong; Lu, Tian Jian
Abstract: Continuous fiber reinforced thermoplastic composite (CFRTPC) auxetic honeycomb structures were fabricated using the 3D printing technology with a specific printing path planning. For comparison, auxetic honeycombs were also fabricated with pure polylactic acid (PLA). In-plane compression tests were conducted, with corresponding damage types explored using Scanning Electron Microscopy (SEM) images. A printing path-based finite element (FE) method was developed to mimic both small and large deformations of CFRTPC auxetic honeycombs, while analytical model was proposed to predict their effective stiffness and Poisson ratio. Good agreement was achieved among analytical predictions, FE simulation results and experimental measurements. A systematic parametric study was subsequently carried out to quantify the dependence of in-plane mechanical properties on geometrical parameters. Compared with pure PLA structures, the presence of continuous fibers efficiently prohibited crack propagation in the matrix for each ligament of CFRTPC auxetic honeycombs. Adding continuous fibers increased the mass only by 6%, but led to dramatic increase in compressive stiffness and energy absorption by 86.3% and 100% respectively and smaller Poisson ratios. The proposed 3D printing technology has great potential in integrated fabrication of continuous fiber reinforced composite lightweight structures having complex shapes, attractive mechanical properties, and multifunctional attributes. Highlights: The continuous fiber reinforced composite auxetic honeycomb was fabricated by 3D printing technology. A combined experimental, analytical and numerical approach was employed to investigate the in-plane behaviors. Adding continuous fibers lead to dramatic increase in mechanical properties and smaller Poisson ratios.